2010
DOI: 10.1111/j.1542-474x.2009.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Maximum Heart Rate Attained during Exercise Testing on Subsequent Heart Rate Recovery

Abstract: There is a relation between the peak heart rate attained during exercise and the subsequent HRR. A low peak heart rate increases the likelihood of a less than normal HRR. Assessment of the entire heart-rate response seems warranted for more thorough risk-stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In the present study, there was no relationship between the peak HR or % maximal predicted HR for age and HRR in athletes, but there was in sedentary controls. Recently, Zaim et al reported a relation between the peak HR attained during exercise and the subsequent HRR in 164 patients who were referred for a symptom-limited standard Bruce Protocol treadmill exercise test, based on clinical indications [14]. Furthermore, our previous study showed the same relationship in 125 obese persons [9].…”
Section: Figuresupporting
confidence: 54%
“…In the present study, there was no relationship between the peak HR or % maximal predicted HR for age and HRR in athletes, but there was in sedentary controls. Recently, Zaim et al reported a relation between the peak HR attained during exercise and the subsequent HRR in 164 patients who were referred for a symptom-limited standard Bruce Protocol treadmill exercise test, based on clinical indications [14]. Furthermore, our previous study showed the same relationship in 125 obese persons [9].…”
Section: Figuresupporting
confidence: 54%
“…independent of other potential physiological mechanisms. 19 Importantly, the greatest improvement in HRR was observed at minute one in recovery. HRR 1 has been suggested to have a strong prognostic power in predicting mortality and closely reflects vagal activity post-exercise, 1,20 which has been suggested to drive the reduction in HR immediately after peak exercise, whereas later in recovery sympathetic withdrawal becomes increasingly important in controlling HR.…”
Section: Discussionmentioning
confidence: 96%
“…Even independent of age, subjects with high peak heart rates have better HRR. 36 Age can therefore be a potential cofounding factor when assessing change in HRR measurement over longer periods (>5 y).…”
Section: Personal Factorsmentioning
confidence: 99%